Comparison of coupon and pipe rack studies for selecting corrosion control treatment. Issue 4 (6th July 2022) - Masters, Sheldon V.; Poncelet‐Johnson, Nicole; Walsh, Ryan; Seidel, Chad J.; Corwin, Christopher J.
Abstract: This study directly compared the data obtained from coupon studies and flow‐through pipe rack studies from two sources in the Denver Water system. The pipe rack study was completed over multiple years using harvested lead service lines. The coupon studies were completed in about 2 months using pure lead coupons. Orthophosphate at 2 mg/L was found to reduce lead concentrations by about 81% in the pipe racks, whereas 74%–81% was observed in the coupons. At an orthophosphate dose of 1 mg/L lead concentrations were reduced by 62%–65% in the pipe loop and by 55%–75% in the coupons, pH at 8.8 reduced lead by 45%–60% in the pipe racks and by 27%–48% in the coupons. The pipe racks were able to give insights into the transition from one condition to another, which is time‐based and dependent on existing pipe scales. Both types of demonstration studies produced similar conclusions about treatment options. The pipe rack was more representative of conditions in the distribution system while the coupon studies were performed in a fraction of the time.